2019
DOI: 10.3390/genes10090702
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Interaction Clusters for MiRNA and MRNA Pairs in TCGA Network

Abstract: Existing methods often fail to recognize the conversions for the biological roles of the pairs of genes and microRNAs (miRNAs) between the tumor and normal samples. We have developed a novel cluster scoring method to identify messenger RNA (mRNA) and miRNA interaction pairs and clusters while considering tumor and normal samples jointly. Our method has identified 54 significant clusters for 15 cancer types selected from The Cancer Genome Atlas project. We also determined the shared clusters across tumor types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…Anti-correlated expressions of 15 cancer types’ miRNA–mRNA pairs from a previous study [ 2 ] were extracted from TCGA ( ), and a total of 65,535 miRNA–mRNA pairs were taken as candidates to be used in subsequent analyses. Because miRNA can repress the expression of its targets, we hypothesize that these anti-correlated miRNA–mRNA pairs are likely to be dysregulated in the observed cancer types, which highlight their potential functional importance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-correlated expressions of 15 cancer types’ miRNA–mRNA pairs from a previous study [ 2 ] were extracted from TCGA ( ), and a total of 65,535 miRNA–mRNA pairs were taken as candidates to be used in subsequent analyses. Because miRNA can repress the expression of its targets, we hypothesize that these anti-correlated miRNA–mRNA pairs are likely to be dysregulated in the observed cancer types, which highlight their potential functional importance.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, in this study, we utilized such anti-correlated miRNA–mRNA pairs identified in a recent study, [ 2 ] to cross-check with publicly available databases—namely dbMTS (database of miRNA target site SNVs) [ 3 ] and dbNSFP (database for nonsynonymous SNPs’ functional predictions) [ 4 ]—for functionally annotated SNVs. This process validated existing cancer related SNVs and identified and prioritized potential SNVs for future functional and experimental validation.…”
Section: Introductionmentioning
confidence: 99%
“…Since PBC is a liver-related trait, we searched the TCGA LIHC dataset [ 19 ] and checked anti-correlated pairs for PTEN targeted miRNA: hsa-mir-590 . We then used hsa-mir-590 to identify its targeted genes in the anti-correlated pair list and obtained 22 additional target genes.…”
Section: Resultsmentioning
confidence: 99%
“…We obtained the mRNA-miRNA pairs in the significant clusters (FDR < 0.1) identified for 15 TCGA cancer types from Dai et al [ 12 ]. The 15 TCGA cancer types studied are bladder urothelial carcinoma (BLCA), breast invasive carcinoma (BRCA or BC), colon adenocarcinoma (COAD), esophageal carcinoma (ESCA), head and neck squamous cell carcinoma (HNSC), kidney chromophobe (KICH), kidney renal clear cell carcinoma (KIRC), kidney renal papillary cell carcinoma (KIRP), liver hepatocellular carcinoma (LIHC), lung adenocarcinoma (LUAD), lung squamous cell carcinoma (LUSC), prostate adenocarcinoma (PRAD), stomach adenocarcinoma (STAD), thyroid carcinoma (THCA), and uterine corpus endometrial carcinoma (UCEC).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we utilized anti-correlated mRNA-miRNA pairs identified in a recent publication [ 12 ] and human sex-biased genes and miRNAs published to date [ 13 , 14 ] to unravel the targeting pattern of sex-biased genes and miRNAs and their potential roles in tumorigenesis and tumor invasion. The prioritized miRNAs and their targeting female-biased genes which have positive correlations with six different immune cell abundance levels could serve as alternative therapeutic cancer markers to design personalized immunotherapy.…”
Section: Introductionmentioning
confidence: 99%